Elective colectomy after colonoscopic polypectomy for unexpected polypoid T1 cancer - Samuolis, Nikas; Samalavičius, Narimantas Evaldas; Mickys, Ugnius (Acta medica Lituanica, 2015)
Purpose. The treatment of early-stage colorectal adenocarcinoma removed endoscopically depends on histopathologic findings. The aim of this retrospective study was to assess the benefit–risk balance to patients who underwent colectomy after endoscopic polypectomy of T1 carcinoma with unfavourable histological factors. Methods. Thirty one patients (15  men and 16 women, median age 66 years) who underwent colectomy after endoscopic resection of malignant polyps with T1 carcinoma within the period from 1 January 2004 Vilnius to 11 February 2015 were included in this retrospective study. Specimens resected after endoscopic polypectomy showed at least one of the following unfavourable factors: no free margin or piecemeal resection. The main objective was to assess the benefit–risk balance of an oncological resection performed after the polypectomy. The oncological benefit was measured by the lymph node metastasis rate. The risk was measured by the occurrence of severe complications of grade III–IV or death. Results. The most common localisation of T1 cancer was sigmoid colon – 16 cases (51.6%) and upper rectum – 11 cases (35.5%). 11 (35.5%) patients had well-differentiated adenocarcinoma (G1), others (20 patients from 31, 64.5%) had moderate differentiated adenocarcinoma (G2). The main indications of colectomy were two: the margin of resection ≤1 mm (n = 23) and piecemeal resection (n = 9). An oncological benefit of colectomy was reached for four patients (12.9%), who had lymph node metastasis. Six patients (19.4%) presented postoperative complications. All of them were of I–II grade according to the Clavien classification. There were no deaths. Conclusions. 12.9% of patients, who underwent oncological colectomy after endoscopic polypectomy for unexpected polypoid T1 cancer with unfavourable histology (no free margin or piecemeal polypectomy), had metastasis in the lymph nodes; thus this study suggests the rationale of an oncological surgical resection after endoscopic polypectomy for these patients.
Keywords: malignant colonic polyp; endoscopic polypectomy; lymph node metastasis